Music Reference Sources: Analog in a Digital World. Issue 4 (1st October 2016) - Scott, Rachel Elizabeth
ABSTRACT: Do we need print reference collections at all? In the case of music reference materials, the answer is definitely "yes." At the University of Memphis, reference titles in the music library are used at about three times the rate of reference materials in the main library. This paper leverages local reference and reserve book usage to investigate how print reference sources support music research of various kinds, how music faculty integrate reference sources into their courses, and how librarians can make finding and using these resources easier for users accustomed to accessing materials online without an intermediary.